Antimicrobial Activity of Triterpenoid and Steroidal Cinnamates from Vitellaria paradoxa - Ojo, Olusesan; Mphahlele, Mokgadi P.; Mmutlane, Edwin M.; Ndinteh, Derek T. (Sciences of Phytochemistry, 2025)
Antimicrobial resistance (AMR) remains a global threat to human health, and its recent burden has necessitated an urgent need for new antibiotics to fight the growing negative impacts of AMR. Vitellaria paradoxa Gaertn. is a medicinal plant used to treat bacterial infections, including diarrhea, tuberculosis (TB), and other respiratory infections in Africa. This study, therefore, assessed the antimicrobial effect and the cytotoxicity of isolated secondary metabolites from the hexane extract of V. paradoxa stem-bark against a panel of bacterial pathogens. After cold maceration, the resulting extract was purified using column chromatography on silica gel. The resazurin-based 96-well plate micro-dilution method was used to assess the antimicrobial activity of the isolated compounds. On further assay, the MTT assay was used to evaluate the cytotoxic effect of compounds on the cervical cancer cell line (HeLa). The column fractionation led to the isolation of 11-hydroxy β-amyrin cinnamate (compound 1), α-amyrin cinnamate (compound 2), and sitosterol cinnamate (compound 3). All the compounds exhibited antibacterial activity against the tested pathogens, with minimum inhibitory concentration (MIC) ranging from 0.0625-1.0 mg/mL. Compound 3 showed the highest antibacterial activity against all bacterial strains (MICs; 0.0625-0.25 mg/mL). The compounds showed no remarkable cytotoxic properties (IC₅₀; 77.82 ± 10.5-82.53 ± 4.07). As far as we know, the results described the antimicrobial activities of compounds 1-3 for the first time. These results provide scientific justification for the traditional uses of V. paradoxa in treating bacterial infections. The highest antibacterial effect of compound 3 highlights its potential as a lead compound.